Edukasi Pemeriksaan Kadar CRP Dengan Sampel Darah Kapiler Pada Petugas Laboraturium RS MMC Palembang - Bastian Bastian; Feronica Putri Pratama; Faaizah Ramadhania (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2022)
Clinical laboratory examination is a system that can determine decisions regarding a disease diagnosis or monitoring of healing through laboratory results. An examination that can help diagnose and detect abnormalities in the body. One of the parameters for examining inflammation markers is C-Reactive Protein (CRP). In the CRP examination, laboratory officers are still using blood samples. However, in addition to venous blood, capillary blood samples can also be used specifically in infant and pediatric patients where CRP levels have the same results as venous blood. As an effort faced by MMC Hospital laboratory workers regarding CRP examination using capillary blood, socialization and education were carried out so that they could increase knowledge and understanding of MMC Hospital laboratory workers. Explanation of material regarding CRP examination using Venous Blood through poster media, and demonstrating at the end of the activity. Keywords: C-Reaktive Protein, Capillary Blood, Inflammation, Laboratory